Method of spiritual ruqyah syar'iyyah as an complementary treatment for depression: contribution in health care sector in the era of globalization - Mohamad, Mohd. Afifuddin (2015)
This paper aims for an in-depth discussion on the Islamic spiritual method, namely the ruqyah syari’yyah, an increasingly popular method used to treat depression. Ruqyah is spiritual treatment process based on the methods that are in line with other religious practices such as prayer and zikr (divine remembrance The objective of the study is to identify the health level of research samples before the treatment, and after the ruqyah spiritual treatments. Method : Research in this study using qualitative methods that combine the use of interview and observation. The process of determining the degree of depression of the sample is through the beck depression inventory (BDI). Result: The study was carried out involving two samples depressed in serious degrees of depression that are marked as samples X and Y which received a score of 50 (extreme depression) and 42 (extreme depression). After ruqyah shar`iyyah spiritual treatment given sample x and y respectively obtain a score of 15 (mild mood disorder) and 8 (normal). Discussion and conclusion: The finding of the study are expected to educate the public about the correct Ruqyah syar'iyyah spiritual treatment methods, as well as to understand the development of alternative treatments that can produce therapeutic effects to people who get mental depression.